2013
DOI: 10.1159/000345957
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Clinical Features of Moyamoya Disease in the USA

Abstract: Background: An increasing number of cases of Moyamoya disease have been reported in the Japanese and US literature. We performed this study to quantify the rise in the prevalence of Moyamoya disease and to study the unique epidemiological and clinical features in the USA that may explain a change in incidence. Methods: We analyzed data derived from patients entered in the Nationwide Inpatient Sample between 2005 and 2008, using ICD-9 codes for Moyamoya disease. Data including patient age, gender, ethnicity, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
70
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 19 publications
7
70
0
1
Order By: Relevance
“…1,68,29,30 In contrast, Asian studies reported higher rates of hemorrhage, ranging from 25% to 62% (Japan, China, and Korea) compared with 10%–29% (Iowa and Hawaii). 3,15,29,31,32 Hemorrhage has been shown to be the most significant factor affecting poor outcome in Asian cohorts, and ruptured thin-walled basal perforators have been cited as the source of high rates of hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…1,68,29,30 In contrast, Asian studies reported higher rates of hemorrhage, ranging from 25% to 62% (Japan, China, and Korea) compared with 10%–29% (Iowa and Hawaii). 3,15,29,31,32 Hemorrhage has been shown to be the most significant factor affecting poor outcome in Asian cohorts, and ruptured thin-walled basal perforators have been cited as the source of high rates of hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies highlighted the differences between MMD presentation in Japanese and American patients. In comparison to Asian cases, Caucasian MMD patients are characterized by an older average age of presentation with lack of bimodal age distribution, prevalence of ischemic stroke type at all ages, more benign presenting symptoms and less common familial occurrence [7][8][9][10][11][12][13][14] . However, the basis of geographical differences in disease occurrence and presentation are still unknown, although environmental and genetic factors have been invoked as possibly influencing factors.…”
Section: Introductionmentioning
confidence: 99%
“…15 Typically moyamoya disease and moyamoya syndrome present during childhood, however the incidence of both forms in North America occurs in the mid-40s. 3 …”
Section: Discussionmentioning
confidence: 99%
“…In general, Moyamoya disease is observed among the various races based on their proportions of the total US population. 3 …”
Section: Introductionmentioning
confidence: 99%